Linking stakeholder perspectives for environmental policy development and implementation in Ghana's gold mining sector: Insights from a Q-methodology study. Issue 97 (July 2019) - Tuokuu, Francis Xavier Dery; Idemudia, Uwafiokun; Gruber, James S.; Kayira, Jean
Highlights: Gold mining has been pivotal to Ghana's development. There is lack of empirical attention on environmental policymaking. We employ the use of Q-sort methodology to quantitatively analyze qualitative perspectives. We find three shared perspectives among stakeholders. We provide the implications of the results for future research in developing countries. Abstract: Gold mining might have contributed to socio-economic development in Ghana, but it has also exacerbated incidences of environmental degradation and fostered associated human rights violations within local communities. As a result, the government of Ghana has sought to address the incidences of environmental degradation related to mining by formulating and implementing a wide range of environmental policies. However, the extent to which these environmental policies have been effective remains debatable. This problem has been attributed to the fact that the views of critical stakeholders were either neglected or received inadequate attention in the design and implementation of environmental policies. Consequently, drawing on empirical evidence from fieldwork in Ghana, and based on Q-methodology, this paper seeks to understand areas of agreements and disagreements among critical stakeholders as a way to improve environmental policy development and implementation. The paper identifies the politics of blaming, regulatory disjuncture and stakeholder expectation dissonance as areas of disagreements within stakeholder views that might also explain the ineffectiveness of environmental policy development and implementation within Ghana's gold mining industry. Similarly, based on the Q-sort factor analysis, the paper synthesizes three perspectives that critical stakeholders believe, if adhered to, could enhance the effectiveness of environmental policies within Ghana's gold mining sector. The paper concludes by considering the implications of its findings for environmental policy development and implementation in developing countries.